The Efficiency Of Google Classroom As Assistant Tool In University Education - Al Boashi, Mohammed; Al Deeb, Saad; Gnedila, Abd Alftah (مجلة العلوم الإنسانية والتطبيقية, 2023)
Many educational institutions have begun to apply technology in their operations, This makes learning continuous and interactive and not limited to place and time. Although building an e-learning platform that is compatible with the organization’s vision and requirements is not easy, there are many e-learning platforms available for free or on the Internet that may fulfill our needs. We just need to test them and look at which platform that will benefit us better. The aims of this research is to study the effect of applying Google Classroom as a supporting tool in university education, and evaluating the impact of the effectiveness of Google Classroom activities on students. The sample included 60 students in the Department of Computer Science. A questionnaire was used to measure the effectiveness of the learning activities available in Google Classroom in three courses (Delphi, Data structures 1, Data structures 2). The results showed that the majority of students were satisfied with the Google Classroom In class . The results of the analyzed data showed that all ratios were higher than average in the areas of Easy access, benefit, communication and interaction, student satisfaction with Google Classroom activities.